2016
DOI: 10.15389/agrobiology.2016.6.763eng
|View full text |Cite
|
Sign up to set email alerts
|

THE HAEMADSORPTION AT AFRICAN SWINE FEVER (review)

Abstract: A b s t r a c tThe capability of causing haemadsorption at African swine fever (ASF) virus (ASFV) reproduction in swine bone marrow cell cultures, leukocytes or continuous cells in the presence of swine erythrocytes is characteristic of the majority of the virus isolates (W.A. Malmquist, D. Hay, 1960). This trait is used for ASF diagnosis based on autohaemadsorption in porcine blood, the virus titration in cell culture, and selection of its attenuated variants in vitro (A.D. Sereda et al., 2014). The haemadso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 25 publications
(28 reference statements)
0
9
0
1
Order By: Relevance
“…Further, the fact that the solid protection afforded by immunization with the Congo-attenuated (KK-262) strain, an SG2 virus, was lost when the Congo CD2v/C-type lectin genes were replaced with those from a virulent France strain (F32), an SG4 virus, directly supports the emerging concept that ASF protective immunity is HAI serotype-specific (Balyshev et al, 1995;Sereda & Balyshev, 2011;Sereda et al, 1992;Vishnjakov et al, 1991;Malogolovkin et al, unpublished data).…”
Section: Immunization With Francementioning
confidence: 95%
See 1 more Smart Citation
“…Further, the fact that the solid protection afforded by immunization with the Congo-attenuated (KK-262) strain, an SG2 virus, was lost when the Congo CD2v/C-type lectin genes were replaced with those from a virulent France strain (F32), an SG4 virus, directly supports the emerging concept that ASF protective immunity is HAI serotype-specific (Balyshev et al, 1995;Sereda & Balyshev, 2011;Sereda et al, 1992;Vishnjakov et al, 1991;Malogolovkin et al, unpublished data).…”
Section: Immunization With Francementioning
confidence: 95%
“…Eight ASFV serogroups (SGs) have been identified, although more are likely to exist (Balyshev et al, 1995(Balyshev et al, , 2010Malogolovkin et al, 2015a;Sereda & Balyshev, 2011;Sereda et al, 1992;Vishnjakov et al, 1995). Notably and of particular significance for vaccine development, ASF protective immunity may be serotype-specific, as viruses of homologous HAI SG appear to cross-protect against one another while heterologous viruses do not (Balyshev et al, 1995;Sereda & Balyshev, 2011;Sereda et al, 1992;Vishnjakov et al, 1991;Malogolovkin A., Sereda A., Balyeshev V. and Kolbasov D., unpublished data). Recently, we have shown that two ASFV-encoded proteins, CD2v (EP402R) and/or C-type lectin (EP153R), are necessary and sufficient for mediating HAI serological specificity (Malogolovkin et al, 2015b).…”
mentioning
confidence: 99%
“…Eight ASFV serogroups (SG) were defined and thoroughly characterized; however, more SG may exist. Additional parameters such as HA density (number of erythrocytes per infected cells) and erythrocyte contact maps were used to refine ASFV isolate classification (Makarov et al, 2016;Sereda et al, 1994). The HAI based assay was used for ASFV strains selection and screening for development a potential liveattenuated vaccine candidates (Sereda et al, 1992;Sereda and Balyshev, 2011).…”
Section: Antigenic Diversity Serogroupsmentioning
confidence: 99%
“…Additional parameters such as HA density (number of erythrocytes per infected cells) and erythrocyte contact maps were used to refine ASFV isolate classification (Makarov et al, 2016;Sereda et al, 1994). The HAI based assay was used for ASFV strains selection and screening for development a potential liveattenuated vaccine candidates (Sereda et al, 1992;Sereda and Balyshev, 2011). Surprisingly, the key significance of HAI classification was discovered even earlier again by Malmquist W.A., who used the HAI assay for ASFV grouping (homologous vs heterologous).…”
Section: Antigenic Diversity Serogroupsmentioning
confidence: 99%
“…Как правило, у природных хозяев, включая клещей, вирус АЧС вызывает субклиническую хроническую или инаппарантную формы инфекции (10,11). Изоляты и штаммы вируса АЧС различаются по патогенным, антигенным, гемадсорбирующим, генетическим свойствам (12)(13)(14). В частности, на основе 3´-концевых последовательностей гена B646L, кодирующего основной капсидный белок p72, в Африке идентифицировано 24 генотипа вируса АЧС (15)(16)(17).…”
unclassified